Examination of gamma-aminobutyric acid and glutamate-glutamine levels in association with impulsive behavior in adolescent marijuana users. (1st April 2022) - Subramaniam, Punitha; Prescot, Andrew; McGlade, Erin; Renshaw, Perry; Yurgelun-Todd, Deborah
Abstract: Background: Adolescent marijuana (MJ) use has been associated with alterations in brain structure and function as well as behavior. Examination of neurochemical correlates such as GABA (gamma-aminobutyric acid) and Glx (glutamate + glutamine) in MJ users remains limited. Impulsivity, identified as a risk factor and consequence of MJ use, has been associated with GABA and Glx levels in healthy and clinical populations. However, this relationship has not been investigated in MJ users. In this study, we examined levels of GABA and Glx in the anterior cingulate cortex (ACC) and its relationship with impulsive behavior in MJ-using adolescents and healthy controls. Methods: Healthy control subjects (HC; N = 21) and MJ-using adolescents (N = 18) completed a metabolite-edited 1 H MRS exam to measure ACC GABA and Glx levels, a structured clinical interview to assess MJ use, and the Barratt Impulsivity Scale (BIS-11) to evaluate impulsive behavior. Results: Adolescent MJ users had significantly lower tissue-corrected GABA (with macromolecules; GABA+) levels ( p = 0.029) compared to HC's. No significant between-group differences were observed in ACC Glx levels. Assessment of impulsive behavior demonstrated no significant between-group differences in motor, non-planning, attention, and total impulsivity scores. Additionally, impulsivity measures and tissue-corrected GABA+ or Glx levels were not significantly correlated in either group. Conclusion: Lower GABA levels in MJ users may indicate alterations in excitatory-inhibitory mechanisms critical for neurodevelopment. Although no significant relationships were observed between impulsive measures and GABA or Glx levels in both groups, further investigations are needed examining the relationship between neurochemical correlates, behavior, and adolescent MJ use. Highlights: Adolescent MJ users showed lower GABA levels in the ACC compared to controls. No significant between-group differences were observed in ACC Glx levels. MJ users and control participants reported similar levels of impulsive behavior. GABA or Glx levels were not significantly correlated with impulsivity in either group. Changes in GABA levels might impact excitatory-inhibitory balance in MJ users.